ANALISIS PENGARUH PENGGUNAAN MEDIA VISUALISASI BERBANTUAN GEOGEBRA DALAM PEMBELAJARAN GEOMETRI PADA SISWA MI/SD - Aida Rahmawati; Anwar Sa'adi; Dinar Binugraheni; Nafisa Tazkia Aulia; Dian Mustika Anggraini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Low interest of elementary school students in mathematics, especially building materials, is still a problem that is quite often encountered, which is generally caused by the presentation of material that tends to be abstract and the lack of utilization of learning media that are able to visualize concepts in an interesting and interactive way. This study aims to examine the use of GeoGebra as a solution in increasing students ' learning interest through a literature study approach with a library study method that analyzes various scientific sources such as journals and relevant research results. The results showed that the use of GeoGebra has significant potential in increasing students ' interest in learning. Because it is able to present spatial visualization dynamically, interactively, and easily understood, and supported by previous research findings that show increased activity, engagement, and enthusiasm of students during learning. Thus, it can be concluded that GeoGebra is an effective and relevant learning medium for use in mathematics learning, especially in building materials in elementary schools.